2021
DOI: 10.3390/ani11113039
|View full text |Cite
|
Sign up to set email alerts
|

Salinity as a Key Factor on the Benthic Fauna Diversity in the Coastal Lakes

Abstract: Benthic communities were studied in nine Polish coastal lakes of the Baltic Sea; representing three levels of hydrological connection with the sea (isolated, periodically connected, and permanently connected), with resultant differences in salinity (freshwater, transitional, and brackish). The lakes classified in this way allowed us to investigate biodiversity in relation to the degree of environmental pressure. Stress intensity in coastal water bodies, resulting from contrasting marine and terrestrial influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The data on taxa and their abundances in the studied BCLs were obtained from an open-access dataset published in studies by 45 , where sampling methods and identification procedures were also included. We had to exclude Oligochaeta and Chironomus n. det, as it is impossible to describe their characteristics precisely.…”
Section: Methodsmentioning
confidence: 99%
“…The data on taxa and their abundances in the studied BCLs were obtained from an open-access dataset published in studies by 45 , where sampling methods and identification procedures were also included. We had to exclude Oligochaeta and Chironomus n. det, as it is impossible to describe their characteristics precisely.…”
Section: Methodsmentioning
confidence: 99%
“…The Baltic coastal lakes can be divided into three main types: (1) open: with permanent connection to the sea through channels/river mouths; (2) intermittently connected: with periodic inflow of seawater thanks to the unblocking of buried channels; and (3) closed: permanently isolated; as well as several subtypes 5 . This hydrological connectivity leads to a variable exchange of substances between the individual ecosystem types, which influences their ecological status depending on the predominance of the marine or terrestrial factor 6 8 . The evaluation of the functioning of microhabitats shaped by the mixing of fresh and brackish water must be based on deterministic chaos theory.…”
Section: Background and Summarymentioning
confidence: 99%
“…Nevertheless, the constant salinity of the southern Baltic Sea (7-8 PSU) leads to the presence of stenohaline organisms, while the salinity in the lakes is generally lower and fluctuates, favoring euryhaline organisms. Therefore, the periodic increase in seawater salinity creates a “window of opportunity” effect for the immigration of marine organisms into the lakes 8 . Among others, there are: the phenomenon of backwash and brackish water intrusion, which causes a periodic change in water quality; the phenomenon of wind support, which hinders or even prevents the outflow of land water into the sea; and the phenomenon of water accumulation on the southern coasts of the Baltic Sea, which is particularly clear during autumn and winter storms.…”
Section: Background and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that salinity is a stress factor for benthic invertebrates (Piscart 2005, Obolewski 2018, Mrozinska 2021. According to those authors, the increase in the salinity gradient generally results in a decreasing trend in the richness and abundance of benthic species, due to the greater instability of environmental conditions in lagoons with marine intrusions.…”
Section: Introductionmentioning
confidence: 99%